Development and Characterization of Eudragit-RL-100-Based Aceclofenac Sustained-Release Matrix Pellets Prepared via Extrusion/Spheronization - Mohamed Abbas Ibrahim (MDPI AG, 2021)
Aceclofenac (AC) is a nonsteroidal anti-inflammatory drug used in the treatment of chronic pain in conditions such as rheumatoid arthritis, with frequent administration during the day. The formulation of sustained release matrix pellets can provide a promising alternative dosage form that controls the release of the drug, with less blood fluctuation and side effects—especially those related to the gastric system. The extrusion/spheronization technique was used to formulate AC matrix pellets. The response surface methodology (version 17.2.02.; Statgraphics Centurion) was used to study the impacts of Eudragit RL 100 and PVP K90 binder solution concentrations on the pellets’ wet mass peak torque, pellet size, and the release of the drug. Statistically, a significant synergistic effect of PVP K90 concentration on the peak torque and pellet size was observed (p = 0.0156 and 0.031, respectively), while Eudragit RL 100 showed significant antagonistic effects (p = 0.042 and 0.013, respectively). The peak torque decreased from 0.513 ± 0.022 to 0.41 ± 0.021 when increasing the Eudragit RL 100 from 0 to 20%, and the pellet size decreased from 0.914 ± 0.047 to 0.789 ± 0.074 nm. The tested independent factors did not significantly affect the drug release in the acidic medium within 2 h, but these pellet formulae maintained the drug release at less than 10% in the acidic medium (pH 1.2), which may decrease gastric irritation side effects. In contrast, a highly significant synergistic effect of Eudragit and highly antagonistic effect of the PVP solution on drug release in the alkaline-pH medium were observed (p = 0.002 and 0.007, respectively). The optimized pellet formula derived from the statistical program, composed of 3.21% Eudragit and 5% PVP solution, showed peak torque of 0.861 ± 0.056 Nm and pellet size of 1090 ± 85 µm, and resulted in a significant retardation effect on the release after 8 h compared to the untreated drug.